2018
DOI: 10.1371/journal.pone.0196644
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the characteristics of network meta-analyses on drug therapy: A systematic review

Abstract: BackgroundNetwork meta-analysis (NMA) is a new tool developed to overcome some limitations of pairwise meta-analyses. NMAs provide evidence on more than two comparators simultaneously. This study aimed to map the characteristics of the published NMAs on drug therapy comparisons.MethodsA systematic review of NMAs comparing pharmacological interventions was performed. Searches in Medline (PubMed) and Scopus along with manual searches were conducted. The main characteristics of NMAs were systematically collected:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Core outcome sets that include measures that track functional impact (e.g., adaptive, executive functioning) are needed to compare results across studies and the impact of treatment on functional outcome (McConachie et al, 2015). As further trials become available (which are needed across more pharmacological agents, e.g., amphetamines), network meta‐analysis may help to guide clinical decision‐making by providing comparisons of different interventions that have not been previously studied using head‐to‐head comparison trials (Cortese et al, 2018; Tonin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Core outcome sets that include measures that track functional impact (e.g., adaptive, executive functioning) are needed to compare results across studies and the impact of treatment on functional outcome (McConachie et al, 2015). As further trials become available (which are needed across more pharmacological agents, e.g., amphetamines), network meta‐analysis may help to guide clinical decision‐making by providing comparisons of different interventions that have not been previously studied using head‐to‐head comparison trials (Cortese et al, 2018; Tonin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In general, there are three types of meta-analysis: (i) pairwise meta-analysis (PW-MA), (ii) network metaanalysis (NMA), (iii) model-based meta-analysis (MBMA). PW-MA is a method that uses a direct (head-to-head) comparison to compare the same interventions [39]. During the recent years, NMA has been used to compare the relative efficacy and safety between treatments.…”
Section: Meta-analysismentioning
confidence: 99%
“…5 Over the past years, NMAs have become more widely used, increasing from fewer than 15 NMAs published per year from 2003 to 2008 to approximately 150 NMAs annually after 2014. 6 However, although high-quality NMAs can produce a broader body of evidence, this technique is resource intensive and time consuming. 7 8 Previous studies have demonstrated that the time between the last systematic search performed by the authors of a systematic review with conventional meta-analysis and the publication of their research is usually greater than 1 year.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Over the past years, NMAs have become more widely used, increasing from fewer than 15 NMAs published per year from 2003 to 2008 to approximately 150 NMAs annually after 2014. 6 However, although high-quality NMAs can produce a broader body of evidence, this technique is resource intensive and time consuming. 7 8 …”
Section: Introductionmentioning
confidence: 99%